2008
DOI: 10.1002/em.20421
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the XRCC1 gene‐environment interactions on DNA damage in healthy Japanese workers

Abstract: X-ray repair crosscomplementing group 1 (XRCC1) has a central role in base excision repair (BER) and single-strand break repair (SSBR). XRCC1 gene polymorphisms (codons 194, 280, and 399) have been identified, and in some cases have been reported to contribute to variations in DNA repair capacity and susceptibility to cancer. To further characterize the effects of XRCC1 gene polymorphisms and their possible interactions with environmental factors on individual levels of DNA damage, we investigated the XRCC1 ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Polymorphisms affecting fundamental cellular processes responsible for maintaining the genomic integrity, such as DNA repair, could be expected to have this kind of effect [80]. Studies demonstrated that environmental exposures may down-regulate expression of some DNA repair genes for XRCC1 [81]. However, these results are more likely due reduced samples observed in non-exposed group.…”
Section: Tablementioning
confidence: 89%
See 1 more Smart Citation
“…Polymorphisms affecting fundamental cellular processes responsible for maintaining the genomic integrity, such as DNA repair, could be expected to have this kind of effect [80]. Studies demonstrated that environmental exposures may down-regulate expression of some DNA repair genes for XRCC1 [81]. However, these results are more likely due reduced samples observed in non-exposed group.…”
Section: Tablementioning
confidence: 89%
“…In our study, non-exposed group presented increased association between XRCC4 Ile/Ile and NPB, and between RAD51 G/C or C/C and MN. Maybe these variants could influence individual DNA repair capacity by interacting with lifestyle factors in healthy subjects [81]. Polymorphisms affecting fundamental cellular processes responsible for maintaining the genomic integrity, such as DNA repair, could be expected to have this kind of effect [80].…”
Section: Tablementioning
confidence: 99%
“…Such results are seemingly consistent with past complementation experiments, in which two out of three studies have found that R280H exhibits an impaired biological function (52–54). Moreover, a few investigations have found that the R280H variant of XRCC1, in contrast to variants R194W or R399Q, imparts a reduced DNA repair capacity phenotype as assessed by the Comet assay (55,56). Thus, although there are mixed reports on R280H, our data supports the evidence that the R280H genotype is more likely a negative risk factor than R194W and R399Q in disease susceptibility, possibly due to a defect in DNA binding.…”
Section: Discussionmentioning
confidence: 99%
“…The base excision repair pathway mainly removes non-bulky base adducts produced by methylation, oxidation or reduction by ionizing radiation or oxidative damage. Several studies [46][47][48] suggested a possible interaction between XRCC1 polymorphisms and environmental factors on cancer risk. The gene-environment interactions have been of great interest to evaluate the exact roles of genetic polymorphisms.…”
Section: Xrcc1 Polymorphisms and Prostate Cancer Risk B Wei Et Almentioning
confidence: 99%